Implementation of Bureaucratic Simplification within the Mahakan Ulu Regency Government - Defri Afrianto (Dinasti International Journal of Education Management And Social Science, 2024)
Various efforts have been made by the government to improve the quality of public services to the community. One thing that was implemented was a bureaucratic simplification policy. In its implementation, not only the central government has to do it, but it also has an impact on regional governments. In fact, Mahakam Ulu Regency, which incidentally is an expansion area, does not receive an exception. This article uses a qualitative approach with data collected through literature study which is then analyzed using qualitative data analysis techniques. In terms of type, this research is descriptive research because it explains various information related to the title of the article written. The results of the analysis show that the Mahakam Ulu Regency Government welcomes the idea from the central government regarding bureaucratic simplification policies with the hope of implementing an efficient and effective bureaucracy so as to provide optimal service to the community. The Mahakam Ulu Regency Government is rushing to realize the mandate of the bureaucratic simplification policy by appointing several administrative officials to be converted into functional officials. In fact, in order to further improve the quality of the bureaucracy so that the idea of ??simplifying the bureaucracy becomes more optimal, the Regent of Mahakam Ulu gave four instructions oriented towards empowering functional positions. However, the implementation of bureaucratic simplification within the Mahakam Ulu Regency Government encountered various problems which resulted in the Mahakam Ulu Regency Government not being ready for the impacts arising from the bureaucratic simplification policy.